A fluorescence enhancement assay for measurement of glutamate decarboxylase activity - Manoochehr Messripour; Azadeh Mesripour (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2020)
Glutamic Acid Decarboxylase (GAD) is an enzyme that converts glutamate to γ-aminobutyric acid (GABA) both in the brain and pancreatic β-cells. Several analytical methods are described for quantitative assay of GAD, where little attention has been given to the enzyme regulation in tissues, in part, due to the complexity of the methods. In this study, a novel fluorimetric method based on changes of fluorescence intensities upon the addition of glutamate substrate into the assay mixture is described. Rat brain GAD was purified and the enzyme activity was determined fluorimetrically in different stages of the enzyme purification. Results showed that during purification steps, changes in fluorescence emission intensities (ΔF/min/mg protein) increased in the paralleled to purification folds of the enzyme. In support of these findings, the levels of CO2 production were measured by Warburg manometric method. The close correlation between the new fluorimetric method and the conventional manometric assay method was demonstrated. Because the proposed fluorimetric method is simple, accurate, and sensitive enough for measuring GAD activity in different stages of the enzyme purification, it would be recommended for the clinical and pharmaceutical investigations.